2023
DOI: 10.3390/foods12122395
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quality and Protein Digestibility of Vegetable Creams Reformulated with Microalgae Inclusion

Abstract: Microalgae are considered a valuable source of proteins that are used to enhance the nutritional value of foods. In this study, a standard vegetable cream recipe was reformulated through the addition of single-cell ingredients from Arthrospira platensis (spirulina), Chlorella vulgaris, Tetraselmis chui, or Nannochloropsis oceanica at two levels of addition (1.5% and 3.0%). The impact of microalgae species and an addition level on the amino acid profile and protein in vitro digestibility of the vegetable creams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Higher consumer acceptance (70%) Vegan kefir Spirulina platensis High lactobacilli and lactococci count [92] Increased total phenolic content of kefir Decreased pH Soy protein isolate hydrogel (SPI) Spirulina platensis Improved rigidity and compactness of SPI hydrogel [121] Plant-based meat alternatives Spirulina and Chlorella Higher gumminess and chewiness [144] Vegetable creams Arthrospira platensis (Spirulina), Chlorella vulgaris, Tetraselmis chui, or Nannochloropsis oceanica Improved protein content and amino acid nutritional profile. No significant differences in protein digestibility [145] Vegan oil-in-water emulsion Spirulina platensis Interesting rheological parameters compared with a more traditional protein source such as chickpea [146]…”
Section: Spirulina and Haematococcusmentioning
confidence: 99%
“…Higher consumer acceptance (70%) Vegan kefir Spirulina platensis High lactobacilli and lactococci count [92] Increased total phenolic content of kefir Decreased pH Soy protein isolate hydrogel (SPI) Spirulina platensis Improved rigidity and compactness of SPI hydrogel [121] Plant-based meat alternatives Spirulina and Chlorella Higher gumminess and chewiness [144] Vegetable creams Arthrospira platensis (Spirulina), Chlorella vulgaris, Tetraselmis chui, or Nannochloropsis oceanica Improved protein content and amino acid nutritional profile. No significant differences in protein digestibility [145] Vegan oil-in-water emulsion Spirulina platensis Interesting rheological parameters compared with a more traditional protein source such as chickpea [146]…”
Section: Spirulina and Haematococcusmentioning
confidence: 99%
“…Studies have shown that adding Spirulina to chocolate [ 25 ] can improve its mouthfeel fragility, with a more pronounced effect observed with increased microalgal content. Similarly, Prandi et al [ 26 ] explored using Chlorella vulgaris , Tetraselmis chui , and Nannochloropsis oceanica in a vegetable cream to maintain its texture while boosting nutritional value. Microalgal proteins have also been looked at as effective emulsifiers in food production; for instance, Rodrigues et al [ 27 ] demonstrated that Spirulina extracts containing phycocyanin could replace traditional additives in ice cream, providing stabilizing properties without compromising consumer acceptability.…”
Section: Microalgal Ingredients For Food Applicationmentioning
confidence: 99%
“…[22][23][24] Many strains of microalgae are rich in vitamins, antioxidants, proteins, and lipids and low in carbohydrates therefore they are considered as healthy food compounds. [25,26] On the global scale, microalgae might help to feed the growing human population, [27] requiring less land for production than common crops or animals [28,29] and can be grown offshore. [30] Microalgae have been used in wastewater cleaning [3] and were tested as pollutant scavengers [31,32] and as a fertilizer for agriculture.…”
Section: Introductionmentioning
confidence: 99%